A game of thrones ebook - Martin, George R. R. (A Song of Ice and Fire, 2003)
NOW THE ACCLAIMED HBO SERIES GAME OF THRONES —THE MASTERPIECE THAT BECAME A CULTURAL PHENOMENON   Here is the first book in the landmark series that has redefined imaginative fiction and become a modern masterpiece. A GAME OF THRONES   In a land where summers can last decades and winters a lifetime, trouble is brewing. The cold is returning, and in the frozen wastes to the North of Winterfell, sinister and supernatural forces are massing beyond the kingdom’s protective Wall. At the center of the conflict lie the Starks of Winterfell, a family as harsh and unyielding as the land they were born to. Sweeping from a land of brutal cold to a distant summertime kingdom of epicurean plenty, here is a tale of lords and ladies, soldiers and sorcerers, assassins and bastards, who come together in a time of grim omens. Amid plots and counterplots, tragedy and betrayal, victory and terror, the fate of the Starks, their allies, and their enemies hangs perilously in the balance, as each endeavors to win that deadliest of conflicts: the game of thrones.   A GAME OF THRONES • A CLASH OF KINGS • A STORM OF SWORDS • A FEAST FOR CROWS • A DANCE WITH DRAGONS